The lived city. Everyday experiences, urban scenarios, and topological networks. - Lindón, Alicia (Geographisch-Ethnographische Gesellschaft Zürich, 2019)
The general subject of this text is the contemporary city, understood as a lived territory. It develops a theoretical--methodological approach to the socio-spatial construction of urban territory that integrates both the material and the nonmaterial. The socio-spatial construction of the lived city is approached via an articulated set of analytical levels. Accordingly, the first part presents the level of the spatial practices and the urban imaginaries that accompany them. The second part integrates the incorporated affectivity that acts and territorializes itself in the everyday life of the city. The third part considers urban scenarios as situational articulations of the subjects of the two previous parts. Individual topological networks are then incorporated as sequences of urban scenarios that integrate the subjects' biography, leading on to the crisscrossing of different topological networks in an approximation of the lived city in all its fragmented, dense, and fluid complexity.
Keywords: Stadtsoziologie; Stadtforschung; Stadttheorie; Urbanistik; Individuum; Handeln; Interaktion; Alltag; Stadtbewohner; Stadtgesellschaft; Alltagsleben; Szenario